2018
DOI: 10.1155/2018/7456857
|View full text |Cite
|
Sign up to set email alerts
|

The Neurodevelopmental Perspective of Surgical Necrotizing Enterocolitis: The Role of the Gut-Brain Axis

Abstract: This state-of-the-art review article aims to highlight the most recent evidence about the therapeutic options of surgical necrotizing enterocolitis, focusing on the molecular basis of the gut-brain axis in relevance to the neurodevelopmental outcomes of primary peritoneal drainage and primary laparotomy. Current evidence favors primary laparotomy over primary peritoneal drainage as regards neurodevelopment in the surgical treatment of necrotizing enterocolitis. The added exposure to inhalational anesthesia in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 85 publications
(97 reference statements)
1
36
0
1
Order By: Relevance
“…The main ischemic and inflammatory diseases described in newborn are necrotizing enterocolitis (NEC), midgut volvulus, focal intestine perforation (Messaoudi et al, 2015;Chen et al, 2016;Wieck et al, 2016). Several published data suggest that in neonates affected by intestinal inflammatory injuries such as Necrotizing Enterocolitis (NEC), a reduced diversity and an altered gut microbiota composition may lead to a pro-inflammatory condition that may play a key role in their pathogenesis (Torrazza and Neu, 2013;Till et al, 2015;Moschopoulos et al, 2018). Despite specific bacteria have not been identified, recent papers have shown that some microbial signatures (e.g., Clostridium spp.…”
Section: Introductionmentioning
confidence: 99%
“…The main ischemic and inflammatory diseases described in newborn are necrotizing enterocolitis (NEC), midgut volvulus, focal intestine perforation (Messaoudi et al, 2015;Chen et al, 2016;Wieck et al, 2016). Several published data suggest that in neonates affected by intestinal inflammatory injuries such as Necrotizing Enterocolitis (NEC), a reduced diversity and an altered gut microbiota composition may lead to a pro-inflammatory condition that may play a key role in their pathogenesis (Torrazza and Neu, 2013;Till et al, 2015;Moschopoulos et al, 2018). Despite specific bacteria have not been identified, recent papers have shown that some microbial signatures (e.g., Clostridium spp.…”
Section: Introductionmentioning
confidence: 99%
“…The recognition of NEC-specific dysbiosis and/or the alteration of the microbiota may allow for a timely diagnosis, targeted treatment, and possibly even prevention or treatment of NEC. Furthermore, the inflammatory cascade induced by microbiota in NEC is considered not to be limited to the gut but may also influence the brain via the so-called bidirectional gut-brain axis [8]. …”
Section: Introductionmentioning
confidence: 99%
“…The poor neurodevelopmental outcomes in infants with NEC may be secondary to a systemic inflammatory response and/or alterations in the gut‐brain axis . Neuronal degeneration in specific regions of the brain and blood‐cerebrospinal fluid barrier disruption occurs after induction of NEC in the preterm piglet model .…”
Section: Implications For Neurogastroenterologymentioning
confidence: 99%
“…59,60 The poor neurodevelopmental outcomes in infants with NEC may be secondary to a systemic inflammatory response and/or alterations in the gut-brain axis. 7,61 Neuronal degeneration in specific regions of the brain and blood-cerebrospinal fluid barrier disruption occurs after induction of NEC in the preterm piglet model. 62 Using the same piglet model, genes associated with neuroinflammation were differentially expressed in the hippocampus following NEC induction, especially when injury is localized in the small intestine.…”
Section: Impli C Ati On S For Neu Rog a S Troenterologymentioning
confidence: 99%